Accurate many-body calculation of electronic and optical band gap of bulk hexagonal boron nitride. Issue 7 (1st February 2019) - Kolos, Miroslav; Karlický, František
Abstract : Benchmark values of quasiparticle and optical gap of bulk h-BN are provided and compared to selected approximative methods. Abstract : Many-body perturbational GW approximation in conjunction with the Bethe–Salpeter equation (BSE) has been employed to calculate accurate electronic and optical band gaps of bulk hexagonal boron nitride (h-BN) in the two most important stacking configurations, AA′ and AB. The carefully converged results revealed h-BN as an indirect material (indirect gap ≈ 6.1 eV) with a huge excitonic effect (≈0.8 eV) in perfect agreement with recent experiments [ Nat. Photonics, 2016, 10, 262; Appl. Phys. Lett., 2016, 109, 122101]. The K – H region of the first Brillouin zone has been shown as the most important for lowest optical excitations in h-BN. Surprisingly, simple scissor corrected DFT has described h-BN band structure at the GW level and subsequent time-dependent DFT with a suitable exchange correlation kernel has provided absorption spectra similar to the full GW+BSE spectra.